2004
DOI: 10.1007/s00468-004-0358-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the leaf miner Cameraria ohridella on whole-plant photosynthetic productivity of Aesculus hippocastanum: insights from a model

Abstract: The leaf miner Cameraria ohridella causes premature defoliation of Aesculus hippocastanum trees. In order to assess the whole-plant loss of productivity caused by the parasite, we monitored seasonal changes of leaf gas exchange and leaf area losses in horse chestnut trees freely infested or chemically treated to prevent moth infestation (controls). Data were integrated in a model and the annual loss of net primary productivity (NPP) was calculated for infested trees with respect to controls. Measurements showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 25 publications
2
38
0
Order By: Relevance
“…1). This attack time course is in accordance with that observed for adult horse chestnut individuals over previous years [9] and has important consequences for plant fitness. In fact, most temperate woody plants complete their leaf expansion and growth by late spring, already, so that any reduction of photosynthetically active leaf surface area after this time can be expected to have limited impact on annual growth.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…1). This attack time course is in accordance with that observed for adult horse chestnut individuals over previous years [9] and has important consequences for plant fitness. In fact, most temperate woody plants complete their leaf expansion and growth by late spring, already, so that any reduction of photosynthetically active leaf surface area after this time can be expected to have limited impact on annual growth.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies [13,16,17] have shown that A. hippocastanum plants attacked by the parasite suffer a major damage in terms of reproductive potential (they produce smaller seeds with limited viability). On the contrary, whole-plant photosynthetic productivity and hydraulics of adult plants did not seem to be heavily affected [13,16], as recently confirmed on the basis of a mathematical model taking into account seasonal changes of photosynthetic rate and damage to foliage [9]. However, little is known of the potential impact of C. ohridella on the hydraulics and productivity of horse chestnut seedlings.…”
Section: Introductionmentioning
confidence: 97%
“…Different leaf-mining depths thus have different impacts on leaf hydraulics, gas exchange, water use and chlorophyll fluorescence (Johnson et al, 1983;Parrella et al, 1985;Trumble et al, 1985;Kappel, 1986;Raimondo et al, 2003Raimondo et al, , 2013Pincebourde et al, 2006;Bueno et al, 2007;Wagner et al, 2008;Lombardini et al, 2013). However, the wholeplant photosynthetic loss from most leaf miners is slight because insect populations are small in natural vegetation (Hileman & Lieto, 1981;Nardini et al, 2004) and the photosynthetic loss does not extend beyond the mined leaf area (Lombardini et al, 2013;Raimondo et al, 2013). While in some economic plants, photosynthesis is negatively correlated with leaf miner density and injury leaf area (Fujiie, 1982;Johnson et al, 1983;Lombardini et al, 2013).…”
Section: Impacts On Plant Physiologymentioning
confidence: 99%
“…One interesting phenomenon is that mined leaves fall earlier than unmined leaves (Owen, 1978;Fujiie, 1982;Maier, 1983Maier, , 1989Nagasaki, 2004;Nardini et al, 2004;Bueno et al, 2007;Wagner et al, 2008). The effects of leaf-mining on leaf life span are stronger than other herbivore guilds .…”
Section: Impacts On Plant Growth and Productionmentioning
confidence: 99%
See 1 more Smart Citation